ONE DAY ONE ARTICLE (ODOA): HABITUATING READING COMPREHENSION SKILLS - Nur Rahmiani (Journal of English Educational Study (JEES), 2023)
This article explores quality habits that can be taught to non-English department students to improve their reading comprehension skills in English-language scientific literature. By using the theory and practice of reading comprehension, students are expected to be able to get used to reading scientific writings in English at a certain stage and time. This paper was developed using a qualitative approach based on data from grounded research that explores phenomena based on inductive studies which include reading theory, reading activity, and reading habit. This study found that students can increase their knowledge by understanding aspects of activities that become routine. These activities are inherent in the quantity and quality of reading activities. The results of this paper have implications for complex literacy mastery in supporting students' higher-order thinking skills (HOTS) as an academic need in the Society 5.0 era. This article proves that there is no barrier for non-English department students to be able to master reading skills from English texts by making quality reading habits.